PENGARUH EKSTRAK SAMBILOTO (Andographis paniculata Nees.) TERHADAP HEMATOKRIT MENCIT (Mus musculus L.) SWISS WEBSTER - eliza, Deni; Sumarmin, Ramadhan; Indriati, Gustina (Pendidikan Biologi, 2013)
ABSTRACTBitter (Androgrhaphis paniculata Nees.) used as a medicinal plant, has a chemical content usefull to the body. One of the active compounds of bitter is andrographolide serves as Immunomodulatory which may affect  to the number of erythrocytes mice. To determine the value of erythrocytes can be seen hematocrit. This research has conducted at Padang State University to determine the effect of extracts of bitter (Andrographis paniculata Nees.) to hematocrit mice (Mus musculus L.) Swiss Webster. This study was conducted in July-August 2013 in the Laboratory of Zoology Department of Biology , Padang State University. This research used Completely Randomized Design (CRD) with 4 treatments 6 replications. The dose were given A = 0 g/mice/day, B = 0.2 g/mice/day, C = 0.4 g/mice/ day, and D = 0.6 g/ mice/day. In this study used male mice (Mus musculus L.) Swiss Webste aged 11-12 weeks. Hematocrit was determined by Microhematocrit. Taking blood by cutting edge mice, aspirated by using a micro hematocrit, then centrifuged at 20,000 rpm. After it looking to the graph. Data were analyzed ANOVA (Analysis of Variance) at level α of 5%. The test results obtained F value 3.79 while the F table 3.10, F count > F 3.10 and conducted further tests with DNMRT (Ducan New Multiple Range Test). Results showed the extract bitter (Andrographis paniculata Nees.) Significantly affected the hematocrit value to mice (Mus musculus L.). In the B (0.2 g/mice/ day)  treatment increased hematocrit, while the enhanced dose treatment C (0.4 g/mice/ day)   and D (0.4 g/mice/ day) there is a decrease, but still above normal (control). It can be concluded that the extract of bitter (Andrographis paniculata Nees.) can increase the hematocrit mice (Mus musculus L.) Swiss Webster.